2012
DOI: 10.3892/etm.2012.514
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of vascular endothelial growth factor for malignant pleural effusion: A meta-analysis

Abstract: Abstract. Since the diagnostic accuracy of conventional examinations for malignant pleural effusion (MPE) is limited, a number of studies have investigated the utility of pleural vascular endothelial growth factor (VEGF) in the diagnosis of MPE. The present meta-analysis aimed to determine the overall accuracy of a VEGF test in the diagnosis of MPE. A systematic review of studies published in English was conducted and the data concerning the accuracy of pleural VEGF assays in the diagnosis of MPE were pooled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 50 publications
(42 reference statements)
0
25
0
1
Order By: Relevance
“…By contrast, VEGF-C and -D are closely associated with lymph vessel neogenesis (8). Previous studies have demonstrated that VEGF-A protein is present in significant amounts in peritoneal and pleural effusions of varying etiologies (9,10). VEGF-A levels in malignant effusions were found to be significantly increased compared with those in non-malignant effusions, indicating that this difference may aid in the differentiation between malignant and non-malignant effusions (11,12).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…By contrast, VEGF-C and -D are closely associated with lymph vessel neogenesis (8). Previous studies have demonstrated that VEGF-A protein is present in significant amounts in peritoneal and pleural effusions of varying etiologies (9,10). VEGF-A levels in malignant effusions were found to be significantly increased compared with those in non-malignant effusions, indicating that this difference may aid in the differentiation between malignant and non-malignant effusions (11,12).…”
Section: Introductionmentioning
confidence: 92%
“…Previous studies demonstrated that an increased level of pleural VEGF-A was associated with malignancy and that VEGF-A was considered to be a marker for the diagnosis of malignant effusion (9,11). VEGF-C and -D are the ligands of VEGF receptor-3 (VEGFR-3) and the latter is localized on lymph-endothelial cells; when VEGFR-3 is activated through the binding of VEGF-C and/or -D, it may to be sufficient to promote the metastasis of cancer cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, conflicting results have been reported (Sack et al 2005), and the exact role of VEGF as a diagnostic marker remains unclear. The results of metaanalysis suggest that VEGF may play a role in the diagnosis of malignant PE, while its diagnostic value is not satisfactory (Shen et al 2012). The combination of VEGF with other markers may aid in the establishment of the diagnosis of malignant PE.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the present study, parapneumonic pleural effusions were excluded and we investigated the role of VEGF in the diagnosis of lymphocytic pleural effusion. Shen et al published a meta-analysis also suggesting that pleural VEGF levels may, to a certain extent, play a role in the diagnosis of MPEs, while its diagnostic value is not satisfactory (37). In this respect, VEGF may be useful as a biomarker of malignancy in exudative pleural effusions.…”
Section: Discussionmentioning
confidence: 99%